Tingkat Pemahaman Masyarakat Lokal sebagai Pemangku Kepentingan Kunci di Tebing Breksi Yogyakarta Terhadap Prinsip-Prinsip Pariwisata Berkelanjutan Berdasarkan SUSTDI - Tania Nugraheni Ayuningtyas (Program Studi Pariwisata Fakultas Ilmu Budaya Universitas Gadjah Mada Yogyakarta, 2018)
Tourism has involved the local communities as a key stakeholders in many tourism destination in Indonesia that are growing due to the phenomenon of digital tourism. In Tebing Breksi Yogyakarta, the growth of tourism sector as a result of the digital tourism phenomenon has made the local people relying on tourism as the main sector to ful l economic needs after the mining ban from the local government. This research conduct the SUSTDI (Stakeholder Understanding of Sustainable Tourism Development Index) method as a tool to asses level of understanding of local communities about sustainable tourism concepts. According to Timur & Getz (2009: 223) about the theory of key stakeholder role, three groups of local community has identi ed such as: host community group, local authority group and tourism industry group. The proportional sampling and strati ed random sampling conducted to determined the amount of representative respondent. The result showed that the local communities as the key stakeholder in Tebing Breksi have a high overall level of understanding about the sustainable tourism concept at the scale 4,19 out of 5,00. Despite of that, the level of understanding on the three of the group respondent on question number 23 implies that the “economic development funds should to be used to promote tourism” as “Medium”. Moreover, tourism planner can use this results to develop a precise education and training program to improve their knowledge about sustainable tourism development.